Scavenger function of resident autofluorescent perivascular macrophages and their contribution to the maintenance of the blood-retinal barrier - Mendes-Jorge, Luísa (2017)
The retina contains two distinct populations of mono-cyte-derived cells: perivascular macrophages, and microglia. The present study was undertaken to evaluate the presence and function in mouse and human retinas of a subtype of resident perivascular macrophages with scavenger function, different from microglia, in physiological conditions and during retinopathy. Perivascular macrophages were characterized by means of confocal microscopy, electron microscopy, and flow cytometry analyses. Two murine models of blood-retinal barrier breakdown and photoreceptor degeneration were used to analyze the role of these macrophages during retinopathy. Results. The macrophages analyzed constituted a small population of resident perivascular cells different from microglia, since they were Iba-1 negative. Although these cells expressed F4/80 and CD11b antigens in common with microglia, they also expressed BM8 and MOMA-2 epitopes, which are mac-rophagic markers not expressed by microglia. Perivascular macrophages emitted autofluorescence due to cytoplasmic inclusions containing protein-bound oxidized lipids. They con-stitutively expressed the scavenger receptor class A and moved along blood vessels, providing an additional coating to thinner areas of the basement membrane. Moreover, they accumulated blood-borne horseradish peroxidase and acetylated low-density. lipoprotein in healthy retinas. In addition, during blood-retinal barrier breakdown and photoreceptor degeneration, these cells migrated to the lesion site. Conclusions. All these morphologic and functional features are consistent with those described for brain Mato cells. Thus, this study showed the presence of autofluorescent perivascular macrophages, different from microglia, with a scavenger function that may contribute to the maintenance of the blood- retinal barrier in healthy conditions and that are also involved in retinopathy.